RF34 Parent and child misperception of child weight status: a cross-sectional analysis of the cork children's lifestyle study (CCLaS). (September 2018) - Kelleher, E; Millar, S; Shiely, F; Perry, IJ; Harrington, JM
Abstract : Background: Despite the increased global awareness of childhood obesity, a high proportion of parents and children continue to misclassify child weight status. The aim of this study was to determine parent and child misperception of child weight and identify the determinants influencing this misperception. Methods: A cross-sectional study involving 1 075 children, aged 8–11 years, drawn from primary schools in Cork city and county in Ireland. Data were collected using child and parent self-administered questionnaires. Physical measurements were taken by trained researchers according to standard procedures. Univariate and multivariable logistic regression analysis was used to examine factors influencing parental and child perceptions regarding child weight. Results: Almost one-quarter of parents of all children misclassified their child's weight status. Forty four per cent of parents of overweight or obese children underestimated their child's weight. In all children, factors associated with parental misperception of child weight included the child being female (OR=1.95; 95% CI 1.36 to 2.81, p<0.001), being overweight or obese (OR=2.84; 95% CI 1.95 to 4.15, p<0.001), child misclassification of own weight (OR=3.28; 95% CI 2.26 to 4.78, p<0.001) and parent reported child computer use (OR=1.64; 95% CI 1.12 to 2.39, p=0.01). In overweight or obese children, accuracy in parental perception of weight improved with increasing child age (OR=0.49; 95% CI 0.27 to 0.88, p=0.02). Of children who were overweight/obese, 76% (n=213) underestimated their weight. These children had increased odds of misperceiving their own weight status if their parents misclassified their child's weight (OR=3.98; 95% CI 1.95 to 8.10, p<0.001). Conclusion: Findings suggest that in an obesogenic society, where overweight and obesity has become the norm, the capacity of both parents and children to correctly classify child weight status is significantly impaired. Health care professionals should be aware of the frequent misperception of weight status, especially when dealing with parents of younger children and children who are overweight or obese.